2020
DOI: 10.1111/1753-6405.13029
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in characteristics in accessing public Australian sexual health services between Medicare‐eligible and Medicare‐ineligible men who have sex with men

Abstract: exually transmitted infections (STIs) are increasing at a significant rate in men who have sex with men (MSM) in Australia. 1,2 Accessible healthcare is a key element of human immunodeficiency virus (HIV) and STI control because it allows timely testing and treatment to prevent ongoing transmission and also access to biomedical HIV preventions. 3,4 Consistent with this are studies showing a reduction in HIV incidence among Australian-born gay, bisexual and other MSM in Australia in the late 2010s after the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
(28 reference statements)
0
11
1
Order By: Relevance
“…53 Given that nurses demonstrated the competencies to provide PrEP, but did not have the prescribing authority to provide PrEP outside of trial conditions, exploring the professional role boundaries in sexual health and PrEP provision services is also warranted. 54 In addressing disparities between different populations acquiring HIV in Australiaparticularly MSM born overseas from Central and South East Asia [35][36][37] a public subsidy of PrEP for all Australian residents (temporary or permanent) would enable equitable financial access to PrEP. This study's findings extend the limited literature on understanding the clinical aspects of providing PrEP in Australia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…53 Given that nurses demonstrated the competencies to provide PrEP, but did not have the prescribing authority to provide PrEP outside of trial conditions, exploring the professional role boundaries in sexual health and PrEP provision services is also warranted. 54 In addressing disparities between different populations acquiring HIV in Australiaparticularly MSM born overseas from Central and South East Asia [35][36][37] a public subsidy of PrEP for all Australian residents (temporary or permanent) would enable equitable financial access to PrEP. This study's findings extend the limited literature on understanding the clinical aspects of providing PrEP in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…5,19,20 In particular, although PrEP has resulted in a significant reduction in new HIV notifications among Australian-born MSM, 2 overseas-born MSM, especially from Central and South East Asia, account for a growing proportion of new HIV notifications, 34 and may have greater difficulty accessing PrEP due to Medicare ineligibility, and 'cultural and language barriers'. 35,36 Survey research shows that men without Medicare in Australia, particularly those born in Asian countries, are overrepresented among those who are willing to use PrEP, but are not actually using it. 37 The primary focus of PrEP delivery in Australia has been on daily PrEP, although on-demand dosing 38 has been included in guidelines as an option for cisgender MSM since 2018.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with previous studies that find that promoting free or reduced-cost HIV services among undertested people who have constrained access to healthcare improves their engagement in the HIV cascade ( 23 , 53 56 ). In Australia, free HIV testing services are available through state government-funded sexual health centres and community-based health services, regardless of their Medicare status ( 21 , 22 ). Raising awareness among migrants of services that offer free HIV care in Australia may help improve testing uptake.…”
Section: Discussionmentioning
confidence: 99%
“…With access to Medicare, migrants from RHCA countries have full access to free HIV testing. In comparison, migrants from non-RHCA countries can access free testing through public-funded programmes that are unevenly distributed across Australia or private insurance, which may require reimbursable upfront payments ( 21 , 22 ). Previous studies found that migrants ineligible for subsidised healthcare through RHCA were more likely to be diagnosed with HIV later than those born in Australia or countries covered by the RHCA agreement ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the US, initiation and adherence to treatment is limited by financial barriers 13 . Conversely, several countries offer free access to antiretroviral therapies and care related to HIV to all temporary residents, 12 including Sweden – notably the first country to achieve 90–90–90 15 . In the wake of the announcement of free access to ART for all temporary residents, 4 Australia is being given the opportunity to set up better support for PLHIV.…”
Section: Discussionmentioning
confidence: 99%